PURCHASE INTENTION OF HALAL LOCAL BEAUTY BRAND DURING COVID-19: THE ROLE OF INFLUENCERS’ CREDIBILITY AND HALAL AWARENESS - Tazlia, Ismi; Nurfadilah, Dety; Pratama, Sasotya (Journal of Islamic Monetary Economics and Finance, 2023)
By applying the Stimulus-Organism-Response (SOR) model, this study investigates whether influencers’ credibility and halal awareness influence customer’s perceived value which, in turn, affects their purchase intention. Gathering data using an online survey and applying the SEM-PLS method, we find that influencers' credibility and halal awareness have a positive effect on the customer’s perceived value for local Indonesian halal beauty products. In addition, the perceived value also affects customers purchase interest.  The results related to halal awareness emphasizes the role of halal certification in the customer’s purchase intention. This study provides valuable insight to the halal local beauty industry to improve the marketing strategy and contributes to the theoretical literature in the field of management and marketing.